EFFECTS OF PERCEIVED ABUSIVE SUPERVISION PERCEIVED MORAL HYPOCRISY AND PROCRASTINATION ON RESEARCH OUTPUT - Amir Waleed; Dr. Muhammad Zafar Iqbal (Policy Journal of Social Science Review, 2026)
This study examined how perceived abusive supervision, perceived moral hypocrisy, and procrastination affected doctoral research output. Focusing on the supervisor–supervisee relationship, it explored how negative supervisory behaviours and ethical inconsistencies shaped research productivity. A cross-sectional quantitative design was used, with data collected from 344 doctoral supervisees and 70 supervisors. The survey instrument was developed and refined through an earlier exploratory phase and validated through expert review and pilot testing. Data were analysed using descriptive and inferential statistics. The findings showed that abusive supervision, moral hypocrisy, and procrastination were significantly associated with lower research output. Regression analysis indicated that abusive supervision (β = −0.182, p = .002), moral hypocrisy (β = −0.213, p = .001),and procrastination (β = −0.156, p = .011) had significant negative effects on research productivity Overall, the results suggest that unsupportive supervision and behavioural tendencies can hinder doctoral research progress. KeyWords: Abusive Supervision, Moral Hypocrisy, Procrastination, Research Output, Supervisor–Supervisee Relationship.